USAGE OF “FISH BONE” DIAGRAM AS EDUCATION TOOLKIT IN LEARNING PROCESS (Proceedings of International Conference on Special Education, 2015)
The purpose of this study is to improve learning process by using "Fish Bone" diagram as an innovative toolkit for education purpose. It has been introduced to increase students’ interest and understanding of the lessons that has been learnt in the classroom. The learning contents would be summarized from selected chapters in every subject and subsequently inserted. The usage of mounting board had been upgraded and improved by using Power Point presentation as a teaching aid. This research had been conducted as a pilot study by using qualitative and quantitative data to support the findings. The researcher does the observation through pop quizzes, assignments and questionnaires to gain respondents evaluation afterwards. The respondents’ for this pilot study were consists of 14 students in semester 2 from College Community Pasir Gudang, who studied in Certificate of Accounting Program. Further, the researcher had summarized Chapter 2 (Build a Frequency Distribution) in Statistic subject. Based on the results, the researcher found that students can improve the quality of learning through a lot of assignments given. While the results were not outstanding, students were able to pass the quiz or tests that were carried out at the time. Usage of “Fish Bone” diagram as education toolkit in learning process was found to be effective if it can be used to summarize selected chapters in each subject.